2016
DOI: 10.1111/bcp.13179
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pharmacokinetic interaction between rilotumumab and epirubicin, cisplatin and capecitabine (ECX) in a Phase 3 study in gastric cancer

Abstract: The results suggest lack of PK-based DDI between rilotumumab and ECX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Etoposide, a widely used drug for SCLC treatment, has been found to possess repressive impacts on the function of CYP3A4 and CYP2C9 [ 17 ]. In clinical practice, special attention is also given to the potential drug interactions between cisplatin, or anti-PDL1 antibody atezolizumab when they are in combination therapy during cancer treatment [ 18 , 19 ]. Patients with cancers are highly susceptible to DDIs due to the co-administration of anticancer drugs with other medications.…”
Section: Introductionmentioning
confidence: 99%
“…Etoposide, a widely used drug for SCLC treatment, has been found to possess repressive impacts on the function of CYP3A4 and CYP2C9 [ 17 ]. In clinical practice, special attention is also given to the potential drug interactions between cisplatin, or anti-PDL1 antibody atezolizumab when they are in combination therapy during cancer treatment [ 18 , 19 ]. Patients with cancers are highly susceptible to DDIs due to the co-administration of anticancer drugs with other medications.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated reports suggest that HGF is important for OC progression, and anti-HGF antibodies have been developed as a targeted OC therapeutics. Several HGF-targeting antibodies, such as Rilotumumab, Ficlatuzumab, and HuL2G have been tested in clinical trials, but they were discontinued because no therapeutic effects were observed in patients with gastric cancer, pulmonary adenocarcinoma, or non-small cell lung cancer (22)(23)(24)(25). Unlike these three antibodies that bind to the HGF β-chain, YYB-101 effectively blocks c-MET signaling by binding to the HGF α-chain involved in the high-affinity binding of c-MET .…”
Section: Discussionmentioning
confidence: 99%
“…The PPCs of drugs used in this study are listed as follows: adriamycin, 0.5 µg/mL; cisplatin, 2.4 µg/mL; gemcitabine, 5 µg/mL; oxaliplatin, 3 µg/mL; 5-fluorouracil, 27 µg/mL. 1721 Each assay was repeated in triplicate.…”
Section: Methodsmentioning
confidence: 99%